2013
DOI: 10.1002/mbo3.111
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of copper availability on bacterial denitrification

Abstract: When denitrifying bacteria such as Paracoccus denitrificans respire anaerobically they convert nitrate to dinitrogen gas via a pathway which includes the potent greenhouse gas, nitrous oxide (N2O). The copper-dependent enzyme Nitrous Oxide reductase (Nos) catalyzes the reduction of N2O to dinitrogen. In low-copper conditions, recent experiments in chemostats have demonstrated that Nos efficiency decreases resulting in significant N2O emissions. For the first time, a chemostat-based mathematical model is develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…This phenomenon has been explored in detail in Pa. denitrificans, where bacterial cultures lacking the trace element copper accumulate significant amounts of N 2 O . Furthermore, mathematical models have been developed that quantitatively predict the levels of N 2 O emitted by bacterial denitrification in response to copper availability (Woolfenden et al, 2013). A recent global transcriptomic study by Sullivan and coworkers has revealed that copper deficiency not only affects functional maturation of N 2 OR, but it has an important impact on gene expression in Pa. denitrificans, including expression of nosZ that is downregulated during copper-limited growth (Sullivan, Gates, Appia-Ayme, Rowley, & Richardson, 2013).…”
Section: Copper and Ph As Emerging Regulatory Factorsmentioning
confidence: 98%
“…This phenomenon has been explored in detail in Pa. denitrificans, where bacterial cultures lacking the trace element copper accumulate significant amounts of N 2 O . Furthermore, mathematical models have been developed that quantitatively predict the levels of N 2 O emitted by bacterial denitrification in response to copper availability (Woolfenden et al, 2013). A recent global transcriptomic study by Sullivan and coworkers has revealed that copper deficiency not only affects functional maturation of N 2 OR, but it has an important impact on gene expression in Pa. denitrificans, including expression of nosZ that is downregulated during copper-limited growth (Sullivan, Gates, Appia-Ayme, Rowley, & Richardson, 2013).…”
Section: Copper and Ph As Emerging Regulatory Factorsmentioning
confidence: 98%
“…In general, fitting a single response variable is straight-forward, but a global fitting for the whole system is much more demanding and challenging to achieve, and even more so if there are different experimental medium conditions jointly with aerobic and anaerobic metabolisms (Woolfenden et al, 2013). We prioritized the diversity of the results because we are convinced that the use of multiple outputs (patterns) to test models is one of the main and most relevant features of the pattern-oriented modelling strategy used in the framework of IBMs (Grimm et al, 2005).…”
Section: Indisim-paracoccus Was Implemented In the Netlogo Platform mentioning
confidence: 99%
“…The global warming potential of N 2 O is 296 times greater than a unit of CO 2 (Richardson et al, 2009). In agricultural soils, N 2 O emissions are of great importance due to the large amount of Nfertilizer in crops and soil organic matter mineralization which depends on the conditions the microorganism encounters in its surrounding environment (Snyder et al, 2009;Woolfenden et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models such as individual-based models (IBMs) [24], [25], [26], [27], metabolic energy-based modelling (EBMs) [28], reaction-centric models (RCMs) [29], and even, deterministic-population models (DPMs) [30] can obtain useful information from a MMR. The reason is that these reactions, or the stoichiometry between chemical species described in the metabolic sub-model, can help in understanding how the microbial interactions happen and why microbial systems behave as they do.…”
Section: Introductionmentioning
confidence: 99%